Applications and Analysis of the Composite wall on Construction in Heilongjiang Province. (2015) - Sun, Shijun; Ma, Dequn; Zhou, Guangchun
Abstract: This paper analysed the results and the status of China's building energy efficiency, explored the new areas of building energy in future: the industrialized composite wall on construction. As China is engaginga process of rapid urbanization, it is believed thatlarge amount of construction will continue for 25-30 years, and all of new buildings must be strictly in accordance with the standards of energy-saving by 50% or 65% in the processes of design and construction. Chinese construction industry is currently implementing the "Four Savings and Environment Protection" policy, which requires energy, land, water and materials saving and environmental protection in every building project. In Heilongjiang Province, as other areas in China, the requirements of energy-efficient design have been comprehensively and strictly implementedon the new buildingssince 2000. By 2010, energy-efficient design has been completely popularized in all kinds of new buildings by 50% energy saving compared with the same type of buildings built in 1980s. According to the requirements of the Ministry of Construction, in the future the further energy efficiency targets should be increased from 50% to 65%, meanwhile the main field of building energyefficiencywill been changed from the initial entry points such as the thermal insulation of externalwall, roof, doors and windows to further wide areas, such as the Optimization of building material, component manufacturing, construction quality and method, all of which could be realized by the industrialized composite panels and walls completely. Industrialized composite panels and wallsbring thoroughgoing innovationson wall materials and construction, the improvementof the construction accuracy, so that the wall thermal insulation performance is much higher than traditional buildings. Due to the productionconcentrated in the factory and the batch processing, the energy consumption ofbuilding industrialization is much lower than the traditional human construction at the construction site. The industrialized composite panel and wall of buildings can reduce the loss of the main materials of construction, the assembling construction reduce the loss of Secondary buildingmaterials. Compared with traditional construction methods, building industrialization of the composite panelrealizesthe field fabricated construction, which greatly minimizes the generation of construction waste, building waste water emissions, construction noise interference, harmful gases and dust emissions, and so on. The Building industrialization could maximize the improvement of the quality of components and assembly precision, and effectively reduce the roof leaks, wall cracks, quality defects of wall and window such as cold air infiltration, so the architectural quality and accuracy can be improved significantly. Factory production and on-site assembling of prefabricated components can reduce the workers of construction site and management, saving a lot of labor costs. Building industrialization transfer most of the operation to production line, saving construction cost and schedule greatly. It is particularly important to the construction in cold areas. Moreover, three types of building composite walls and panel are introduced. In this paper, composite walls and panel include composite material, composite structure or both of them applied in the wall and panel. The first kind of composite wall is the straw board. The straw board is clean, which is made of natural straw or wheat straw as the main raw material. This kind of straw board is mainly used for internal and external walls of the building and roof of the building, etc. Straw board whichis regarded as wall materials generally does not work as load-bearing walls. When it comes to application, the surface should be decorated to ensure that its fire, moisture, fire-retardant abilities. Straw board is not only suitable for load-bearing frame structure buildings, including civil construction, light industrial plants, but also for the old buildings which need to be rebuild, storage buildings and temporary buildings, etc. It is a lightweight, high strength, thermal insulation board which is new and environmentally friendly, particularly suitable to use in cold regions construction. The second example is the HS-EPS core column structure system, whichis invented by Harbin Hong Sheng housing energy system research and development centre with the whole intellectual property patents. This system consists of base beam, EPS moulded wall composed with core column of reinforced concrete, eaves ring beam and roof trusses and other components, is suitable for various types of single storeybuildings.EPS module consists of polystyrene beads by heating and foaming, through a dedicated heat moulding equipment and moulds in the system with closed-cell structure of different types, different specifications and different shape. The modules are rectangular, which internal and external surfaces distribute the uniform dovetails. There are two bridges connecting the fixed plug door in the middle of three 200 mm × 240 mm rectangular hole, both inside and outside of the hole wall thickness is 50 mm. In 2010, itwas applied in Piaohe town as a pilot project and in Antu County as 800 post-disaster housing, where thissystem has been widely recognized. The third sample is Gao Ge Composite Panel of Husk Mortar, with the both advantages of composite material and composite structure. This panelis precast, made from light husk mortar, welded wire mesh and steel as the skeleton, and thermal, noise insulation layers. The husk mortar is made of cement, sand, husks and water by mixing. This panel can be used to the wall-bearing housing, and multi-storied and high-rise reinforced concrete frame construction as the envelope, its overall size is the same with the external wall of a room, as in Four sides of the panel are joined with the beams and columns of the buildings. The wall panel consists of two surface layer of husk mortar, and two insulation layer (benzene or rock cotton) and a air layer inside. The two surface layers are connected by the vertical and horizontal reinforced ribs, and the insulation layers are spliced inside by mortar, each small insulation board was totally fixed by insulation mortar from 5 surfaces. The cavities between two insulation layers are supported by the ribs.